Pembelajaran Berbasis Komunitas Lembang Raru Sibunuan Kecamatan Sangalla` Selatan Kabupaten Tana Toraja - Ariantho Rekan Palallo; Lilisda Sampe; Rati Pundissing; Westerini Lusdani (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Learning is assistance provided by educators so that the process of acquiring knowledge and knowledge, mastering skills and habits, as well as forming attitudes and beliefs in students can occur. Learning is a process to help students learn well. Community-based learning is a group of educators and education personnel in one school who study together and collaborate regularly with clear and measurable goals to improve the quality of learning so that it has an impact on student learning outcomes. The aim of this activity is to increase the competence of educators and build a culture of sustainable learning together, so that it has an impact on improving student learning outcomes. Community-based learning is very important because the learning community is a forum for realizing collaboration between students. With a learning community, students can gain quality learning experiences.